Global research on submarine landslides, 2001–2020 - Chen, Wenwen; Xing, Junhui (Frontiers in Earth Science, 2023)
Submarine landslides, one of the hotspots in marine geoscience research, are one of the most harmful marine geological disasters. To understand the research status and further research directions of submarine landslides, this paper analyzed the global submarine landslide-related work during the period from 2001 to 2020. To achieve this objective, Science Citation Index Expand and the Social Sciences Citation Index, belonging to the WoS Core Collection, were the two bibliographic databases selected as a reference. In this study, we focused on document types, publishing languages, subject categories, journals’ productivity, countries and author, and co-occurrence keywords network. Geoscience multidisciplinary, Geochemistry Geophysics, Oceanography, Environmental Sciences, and Materials Science Multidisciplinary have been the most commonly used science categories in the past two decades. Marine Geology, Marine and Petroleum Geology, Journal of Volcanology, and Geothermal Research are the three most productive journals on submarine landslides. Marine Geology is the most active journal among all the journals. The United States, the United Kingdom, China, Germany, and France are the five most productive countries. At the institutional level, the Centre National De la Recherche Scientifique (France) is the most active institution, followed by the Chinese Academy of Sciences (China) and Helmholtz Association (Germany). Masson DG and Talling PJ from the United Kingdom contribute to the most high-quality submarine landslide-related publications. Analyzing by CiteSpace, the five largest clusters in the submarine landslide field are “gas hydrate,” “turbidity current,” “thin film,” “debris avalanche,” and “submarine canyon.” Active further research directions of submarine landslides are “south china sea,” “slump,” and “submarine mass failure.”